A Study on the Perception of African Elephant (Loxodonta africana) Conservation by School Children in Africa and England (UK) - Katie E. Thompson; Genoveva F. Esteban (Diversity, 2023)
Environmental education (EE) applications can support wildlife conservation practices by improving school children’s understanding of environmental issues, including endangered species conservation, such as the African savanna elephant (Loxodonta africana). This study aimed to identify and assess school children’s perceptions of elephant conservation in three schools: South Africa, Kenya, and England. Questionnaires were completed by students at one school per location, with the age range of 10–16 (n = 364). The responses were then analysed independently and collectively using descriptive statistics (n = 364). School children feared elephants where elephants were native. The importance of elephants was not acknowledged by students in South Africa and England and included a lack of awareness of how elephants benefit other species. There was an unclear understanding of the threats to elephants. Collectively, a wildlife guide as a career choice was not highly valued. The results of this study have reflected key narratives of elephant conservation from selected countries; Kenya leading in anti-poaching and anti-trade campaigns, anti-poaching campaigns by various NGOs in the U.K., and elephant management around expanding populations in South Africa, which have given significant insights into areas of improvement for environmental education practices to support wildlife conservation globally. Furthermore, this new research has identified and compared school children’s awareness of elephant conservation on a greater spatial scale than what is currently understood, compounding the importance of understanding effective wildlife conservation in education.